2017
DOI: 10.1038/s41598-017-02441-5
|View full text |Cite
|
Sign up to set email alerts
|

Callistemenonone A, a novel dearomatic dibenzofuran-type acylphloroglucinol with antimicrobial activity from Callistemon viminalis

Abstract: A new acylphloroglucinol with a novel architecture including an unprecedented dearomatic dibenzofuran core, named callistemenonone A (1), was isolated from the leaves of Callistemon viminalis (Myrtaceae). The structure was fully characterized on the basis of extensive spectroscopic analysis, including UV, HRESIMS, as well as 1D and 2D NMR spectral data (HSQC, HMBC, and ROESY). The deduced structure represents the first example of a natural dibenzofuran with two phenyl moieties coupling through tertiary hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Based on the fact that numerous species in the Myrtaceae family exploit an antibiotic advantage by targeting the bacterial membrane, , comprehensive investigations were conducted to further understand the antimicrobial mechanism of 1 and 2 against clinical MRSA (JCSC 4744).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fact that numerous species in the Myrtaceae family exploit an antibiotic advantage by targeting the bacterial membrane, , comprehensive investigations were conducted to further understand the antimicrobial mechanism of 1 and 2 against clinical MRSA (JCSC 4744).…”
Section: Resultsmentioning
confidence: 99%
“…The MIC and MBC evaluations, a time–killing study, a cytoplasmic membrane depolarization experiment, a SYTOX green assay, and scanning electron microscopy studies on compounds 1 and 2 were carried out according to the standard methods. Detailed procedures are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of callistemenonone A and melittin (a small peptide from bee venom) has been shown to have a synergistic effect against MRSA; however, the effect was minor. 58 Similarly, Lee et al 133 reported synergistic killing of methicillin-sensitive and methicillin-resistant S. aureus when dieckol was combined with β-lactams such as ampicillin or penicillin. Another compound, eckol, found in ethyl acetate extracts of Ecklonia cava, when combined with ampicillin, has a synergistic impact against S. aureus and an additive effect against Salmonella Typhimurium.…”
Section: Application Of Pg and Its Derivativesmentioning
confidence: 98%
“…Among them, oligomerization of acylphloroglucinol leads to dimeric or trimeric phloroglucinol compounds. 14,15 It could also be conjugated with terpene units through hetero- or carbo-[4 + 2] or [3 + 2] cyclization to afford acylphloroglucinol–terpenes. 16,17 Polycyclic polyprenylated acylphloroglucinols (PPAPs) are generally biosynthesized from C -cyclization of prenylated acylphloroglucinols.…”
Section: Introductionmentioning
confidence: 99%